The Checklist of Canterno lake. Update to December 2020 (Southern Latium) - De Pisi, Ermanno; Marozza, Luigi (BORNH Bulletin of Regional Natural History, 2021)
This study was carried out in the Canterno lake (Lat 41° 45’10,9’’ N - Long 13° 15’ 1,5’’ E) in the 2018 – 2020 period. 133 species (72 Non-Passerines - 54,5% - and 61 Passerines 46,2%) were recorded. 124 species are in the Red List of Italian breeding birds, 31 species are listed in Annex I of the Directive 2009/147/EC on the conservation of wild birds. The data shows the presences of Ciconia nigra, Coracias garrulus, Clamator glandarius, Accipiter gentilis, Tadorna tadorna, Tadorna ferruginea and the regular migration of Pandion haliaetus, Hieraaetus pennatus, Falco vespertinus and Ficedula albicollis. 41 species have a status of resident and breeding; 19 species are summer breeding visitors; 26 are migrant species; 16 species are wintering. The data integrate the last published checklist (Roma & Rossetti 1998) making a review of the waterbirds list. The list adopts the systematic classification and the italian common name of the recently check-list of birds of Latium (Brunelli et al., 2019).